Calculating the value of heat energy from agricultural wastes and fat dregs from grease trap of food courts - โกศลานันท์, สำรวม; ปราโมทย์, พิพัฒน์; พัฒนะอิ่ม, ณัฐสิทธิ์ (Frontiers in Engineering Innovation Research, 2010)
This research examined the heat value of agricultural wastes : chaff, saw dust, cassava root and corncob comparing to the heat value of fat dregs from fat dregs from grease trap of food courts. The result shows that fat dregs from grease traps mixing between vegetable fat and animal fat have the value of heat energy 15.50 kJ. In contrast, the value of heat energy agricultural wastes are the value of heat energy 11.47 kJ for chaff, 13.87 kJ for saw, had the heat value about 12.33 kJ for cassava root and 14.10 kJ for corncob.